Commercial vehicle parking duration in New York City and its implications for planning. (October 2018) - Schmid, Joshua; Wang, Xiaokun (Cara); Conway, Alison
Abstract: Freight vehicle parking has long been an issue in urban areas; however, literature is limited and little attention has been paid to parking duration. Using field-collected freight parking observation data from New York City, this study estimated a parametric survival model to predict parking durations based on several characteristics of a parked freight vehicle. Results indicated that vehicles delivering different types of items parked for differing durations, while vehicles that parked illegally were likely to park for a shorter period of time. The model was then employed to make predictions regarding how parking durations would differ based on vehicle and delivery characteristics. An elasticity analysis was performed on each significant variable, and planning recommendations were made in order to maximize the amount of vehicles parking legally. Recommendations for future research included expanding the dataset to obtain more accurate estimates and applying the duration model to optimize operations at a business or logistics firm.